2011
DOI: 10.1002/poc.1955
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced decarboxylation of 9‐oxo‐6,9‐dihydro[1,2,5]selenadiazolo[3,4‐f]quinoline‐8‐carboxylic acid

Abstract: Photoinduced reactions of 9‐oxo‐6,9‐dihydro[1,2,5]selenadiazolo[3,4‐f]quinoline‐8‐carboxylic acid (SeQCA) were investigated in alkaline media (aqueous NaOH solutions) by electron paramagnetic resonance (EPR) spectroscopy, following the in situ formation of paramagnetic species. According to UV–Vis and nuclear magnetic resonance investigations, protonation (pH ≈ 11) and deprotonation (pH ≈ 13) of the imino hydrogen of the 4‐pyridone moiety has to be considered, reflected also in the different EPR spectra observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Introducing the selenadiazole ring to a 4‐oxoquinoline moiety was expected to enhance the biological activity and to affect the desired photoactivity, via shifting the absorption bands to the visible region. Based on these presumptions, a group of selenadiazoloquinolones were synthesized and studied in our laboratories previously . Detailed investigation of their photoinduced processes confirmed that these compounds can behave as photosensitizers, generating ROS in the presence of molecular oxygen upon UVA irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…Introducing the selenadiazole ring to a 4‐oxoquinoline moiety was expected to enhance the biological activity and to affect the desired photoactivity, via shifting the absorption bands to the visible region. Based on these presumptions, a group of selenadiazoloquinolones were synthesized and studied in our laboratories previously . Detailed investigation of their photoinduced processes confirmed that these compounds can behave as photosensitizers, generating ROS in the presence of molecular oxygen upon UVA irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In our previous research, 7-substituted selenadiazolo [3,4-h]quinolones and 8-substituted selenadiazolo [3,4-f]quinolones (R 7 , R 8 = H, CN, COCH 3 , COOMe, COOEt, COOH) were successfully synthetized by the GouldJacobs reaction 7,8 and their biological/photobiological activity was investigated together with their EPR spectroscopy. [9][10][11][12] Antimicrobial activity of 7-substituted selenadiazolo [3,4-Analogously, treatment of selenadiazoloquinolone 4 with EtI in the presence of K 2 CO 3 afforded a mixture of N-and O-ethylated products 5 and 6 in almost the same ratio as in the previous case. Despite the fact that formation of selanadiazoloquinoline 6 was not observed when NaH was applied as the base, desired 6-ethylselenadiazoloquinolone 5 was isolated only in 26% yield (Scheme 2).…”
Section: Introductionmentioning
confidence: 60%
“…[6][7][8][9][10] Previously, we synthesized a series of novel substituted quinolones and fused selenadiazoloquinolones and investigated the influence of their structure and various substitutions on their chemical, redox, photochemical and biological properties. [11][12][13][14][15] The oxidation of organic nitrogen-containing compounds using oxygen transfer agents like peracids or hydrogen peroxide is intensively applied in synthesis. [16][17][18] The products of the oxidation of amines vary depending on their structure, producing a wide range of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These have a broad spectrum of activity against Gram‐positive and Gram‐negative bacteria; thus, they have been successfully used to treat various infections, respiratory diseases and tuberculosis . Previously, we synthesized a series of novel substituted quinolones and fused selenadiazoloquinolones and investigated the influence of their structure and various substitutions on their chemical, redox, photochemical and biological properties …”
Section: Introductionmentioning
confidence: 99%